2014
DOI: 10.1016/j.jconrel.2014.08.011
|View full text |Cite
|
Sign up to set email alerts
|

The potential of antigen and TriMix sonoporation using mRNA-loaded microbubbles for ultrasound-triggered cancer immunotherapy

Abstract: Dendritic cell (DC)-based cancer vaccines, where the patient's own immune system is harnessed to target and destroy tumor tissue, has emerged as a potent therapeutic strategy. In the development of such DC vaccines, it is crucial to load the DCs with tumor antigens, and to simultaneously activate them to become more potent antigen-presenting cells. For this, we report on microbubbles, loaded with both antigen mRNA as well as immunomodulating TriMix mRNA, which can be used for the ultrasound-triggered transfect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
78
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 101 publications
(80 citation statements)
references
References 47 publications
(60 reference statements)
2
78
0
Order By: Relevance
“…Nevertheless, studies in the field of cancer immunotherapy have demonstrated that neither sono-nor electroporation results in strong activation of immune cells. In fact, both techniques require additional stimulation with adjuvants to induce therapeutically beneficial immune responses [79,80]. This might indicate that cytosolic PRRs are less immunogenic than endosomal TLRs.…”
Section: Mrna Delivery Methodsmentioning
confidence: 99%
“…Nevertheless, studies in the field of cancer immunotherapy have demonstrated that neither sono-nor electroporation results in strong activation of immune cells. In fact, both techniques require additional stimulation with adjuvants to induce therapeutically beneficial immune responses [79,80]. This might indicate that cytosolic PRRs are less immunogenic than endosomal TLRs.…”
Section: Mrna Delivery Methodsmentioning
confidence: 99%
“…It has been demonstrated that transfection is significantly enhanced using microtubules, and US can activate powerful immune responses in vivo, which can be applied as a potential method for further clinical trials (Figure 3). 50 Oda et al used microbubbles combined with US irradiation to deliver antigens that were extracted from tumor cells into DCs and then investigated the therapeutic effect of the treated DCs on a mouse model of lung metastasis. The results demonstrated that prophylactic immunization with this strategy showed significant suppression (a four-fold decrease) of melanoma lung metastases 51…”
Section: Immunotherapy Assisted By Ummdmentioning
confidence: 99%
“…Cancer cells are easy to culture and to manipulate and therefore useful for fundamental studies. Finally, dendritic cells 14 or lymphocytes 22 are also interesting targets, e.g., for immunotherapy, since these can be reached directly from the blood stream or from the lymphatic nodes after subcutaneous injection and drainage of the microbubbles.…”
Section: Choice Of the Cell Modelmentioning
confidence: 99%